3D PRINTING OF BUILDINGS: CONSTRUCTION OF SUSTAINABLE HOUSES OF THE FUTURE BY BIM - Soundarya Metre; Mohd Osman; Sunil Kumar Birkur; Channappa (International Educational Journal of Science and Engineering, 2026)
3d printing building technology is a new construction technique started with the invention of 3D printer. Latest technologies were described pointing to Contour Crafting as a promising technique that may be able to revolutionize construction industry in near future. It has many advantages of this technology, such as reduction of the costs and time, minimizing the pollution of environment and decrease of injuries and fatalities on construction sites could be listed. Integration of Building Information Modeling with the 3D printing building technique are mentioned in comparison with the traditional construction techniques. Even though many advantages and benefits of this new technology, of course we have some concerns that are summarized in the conclusions as the technology still has many limitations. A brief description of examples of 3D printing in construction industry are presented (Stupino town, Moscow, Russia - Apis Cor first company to develop a mobile construction 3D printer). Modeling a 3D model of building that will be appropriate for 3D printers is possible in many modeling software programs. One of the most popular formats for sharing such models is STL format common and it has been accepted by many proprietary software. Moreover, integration of BIM method with 3D printing modeling will be effective for energy efficiency, better design, cost reduction and isolation of structure.